Influence of the Food to Microorganisms (F/M) Ratio Andtemperature on Batch Anaerobic Digestion Processes Withandwithout Zeolite Addition - Montalvo-Martinez, S (2012)
The main objective of this work was to evaluate the influence of the food to microorganisms (F/M) ratio and temperature on batch anaerobic digestion processes carried out with and without zeolite addition as a microbial carrier. Three laboratory-scale experimental runs were conducted using a synthetic substrate with a COD:N:P ratio of 500:5:1. The first run (I) was conducted at a constant temperature of 27°C, increasing the F/M ratio from 0.21 to 0.40 (g COD/g VSS). During the second run (II) the temperature and the F/M ratio increased from 27°C to 37°C and from 0.21 to 0.40, respectively. Finally, in the third experimental run (III) the F/M ratio achieved high values (1.92 and 1.30) either by varying the substrate concentration at a constant biomass concentration or by increasing the biomass concentration at a constant substrate concentration. Higher biomass growth rate, COD removal and methane production were found in the reactors with zeolite, especially at the highest F/M assayed during the first run. The highest ammonium removals were also achieved at the highest F/M ratio (0.40) in the reactors with zeolite. Within the range studied (25°C-37°C) in the reactors with zeolite operating at 37°C, the second run demonstrated the low influence of temperature on substrate consumption and ammonia removal, with 93% and 70% of COD and ammonia removal efficiencies, respectively. The third run corroborated the results previously obtained and fit the experimental results to simple kinetic models, the Monod model being the most adequate for predicting the behavior of the systems studied. The maximum specific microorganism growth rate (?max) values for the reactors with zeolite were almost twice as high as those obtained for the reactors without zeolite for similar F/M ratios. Copyright © 2012 Taylor and Francis Group, LLC.
Keywords: Anaerobic processes; zeolite; kinetics; food/microrganisms ratio; temperature